A New De-Noising Method for Ground Penetrating Radar Signal. Issue 2 (March 2021) - Ma, YongMin; Jong, YongGwang; Liu, Yang
Abstract: The de-noising of data has become the key problem of ground penetrating radar (GPR) research. In this paper, the de-noising method based on combination of complete ensemble empirical mode decomposition (CEEMD) and wavelet decomposition is proposed. By combining CEEMD and wavelet decomposition, the effective signal information can be extracted from the removed intrinsic mode function (IMF) components in de-noising based on CEEMD. Numerical simulation results show that the quality of the GPR signal can be obviously improved by using the combination method.